2012
DOI: 10.1111/j.1753-4887.2012.00492.x
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide consumption of functional foods: a systematic review

Abstract: The present systematic review was performed to assess differences in the worldwide consumption of functional foods. The Medline and Scopus databases were used to search the existing literature. A total of 23 studies that examined functional food consumption and included information on the country, gender, and age of participants were identified for inclusion. The studies investigated a variety of functional foods, and analysis of the findings indicates it is not possible to reach generalized conclusions about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
129
1
20

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(155 citation statements)
references
References 55 publications
(260 reference statements)
5
129
1
20
Order By: Relevance
“…As for the PE, high income and high education is associated with positive consumer behaviour (Hung, de Kok & Verbeke, 2016;Hur and Jang, 2015;JezewskaZychowicz & Krolak;Schnettler et al, 2015). As for age and gender, three systematic reviews on functional foods, including studies covering different product categories (Kaur & Singh, 2017;Ozen et al, 2014) concluded on the difficulty to identify how the two characteristics influence the consumption of Ffs. Recently Bimbo et al (2017), by focusing on functional dairy products, concluded that female and older consumers are more likely to be willing to try and to include Ffs in their diet.…”
Section: Functional Foodsmentioning
confidence: 99%
“…As for the PE, high income and high education is associated with positive consumer behaviour (Hung, de Kok & Verbeke, 2016;Hur and Jang, 2015;JezewskaZychowicz & Krolak;Schnettler et al, 2015). As for age and gender, three systematic reviews on functional foods, including studies covering different product categories (Kaur & Singh, 2017;Ozen et al, 2014) concluded on the difficulty to identify how the two characteristics influence the consumption of Ffs. Recently Bimbo et al (2017), by focusing on functional dairy products, concluded that female and older consumers are more likely to be willing to try and to include Ffs in their diet.…”
Section: Functional Foodsmentioning
confidence: 99%
“…Thus, the present doses equates to 3-10 cups of prepared tea. Approximately 15%-55% of individuals in the United States drink tea (Duffey and Popkin 2007;Ozen et al 2012) with a mean intake of 23-30 mg caffeine per day from tea (Frary et al 2005;Fulgoni et al 2015). However, in other countries, such as the United Kingdom, anecdotal evidence suggests that tea intake may reach 6-9 cups per day (Khokhar and Magnusdottir 2002).…”
Section: Limitationsmentioning
confidence: 99%
“…A systematic review study yielded that functional foods are generally accepted by nutritional professionals. However, further study is required into the discrepancies between dieticians and experts in human nutrition regarding the view that it is "dangerous" to consume certain functional foods and regarding their evaluation of whether the public know in which situations certain functional foods should be consumed [14]. Red ginseng is one of the most widely consumed health functional foods, in addition to multivitamin, omega-3, glucosamine and others.…”
Section: Introductionmentioning
confidence: 99%